STUDENTS' REFLECTION ON GREEN SCHOOL - Abdul Razak, Nurul Hafiffah Bt.; H. Iksan, Zanaton; Syed Zakaria, Sharifah Zarina (Journal of Techno-Social, 2017)
Education plays an important role in enhancing sustainable development and improving human capacity in addressing the issues of environment. Environment and development need to be incorporated as a key component in learning fields. Environment and Sustainability Course (GGGR6223) is a course offered to postgraduate students who are taking Science Education at the Faculty of Education, Universiti Kebangsaan Malaysia (UKM). This course prepares students with the knowledge, skills and approaches in management and environmental sustainability, especially on renewable and non-renewable resources as well as the problems that exist due to human activities. This study aimed to review the reflections made by the students of Environment and Sustainability Course at the National University of Malaysia on Green School. Data were collected through reflections made by the students upon completion of tasks and lectures related to green school carried out in their school. A total of 26 students' reflections were analyzed. Thematic analysis resulted in five key dimensions: positive feelings, awareness of green schools, understanding of green school's concepts, the role of teachers in instilling awareness about green schools and challenges in its implementation. The analysis demonstrated that the students have been exposed and have proper awareness about green schools. Awareness of green schools and environmental education are expected to form the next generations who are able to appreciate life and the environment.